THE IMPACT OF HERDING BEHAVIOR AND OTHER BEHAVIORAL BIASES ON CAPITAL MARKET DECISIONS IN GENERATION Z STUDENTS - Sihotang, A. E; Pertiwi, T. K. (Economics and Statistics Research Journal (ESRJ), 2023)
This study examines the impact of behavioral biases, such as overconfidence, regret aversion, loss aversion, and herding behavior, on investment decision-making in Generation Z students. It also explores the moderating role of risk perception in the relationship between these biases and investment decisions. Data was collected from 120 respondents through a questionnaire-based survey, and the Partial Least Square method was used for analysis. The results indicate that while overconfidence has a significant positive impact on investment decisions, regret aversion, loss aversion, herding behavior, and risk perception have a non-significant effect. The study highlights the importance of understanding behavioral biases in investment decision-making among Generation Z students and the role of risk perception in moderating the impact of these biases on investment decisions. Moreover, it contributes to the growing literature on behavioral finance and its implications for the capital markets.